Assessing Value for Money: the Oxford Policy Management Approach - and King, Julian (Daniel Wate, 2023)
This document offers practical guidance for assessing the Value for Money (VfM) of government- and donor-financed programmes and policy interventions. In line with OPM’s focus and mission, it has been predominantly applied in the international development sector, but the approach upon which it is based is also used in the context of domestic public policy and programmes.1 There is increasing scrutiny on VfM in international development, but a lack of appropriate methods to support its assessment. There is a risk of reaching invalid conclusions if VfM evaluation is tied to a narrow set of indicators devoid of any evaluative judgement—for example, by emphasising the most readily quantifiable measures rather than the most important (but harder to quantify) aspects of performance, or by focusing on the quantification of outputs and outcomes at the expense of more nuanced consideration of their quality, value, and importance. The approach presented in this guide combines theory and practice from evaluation and economics to respond to requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management. It involves developing and implementing a framework for: organising evidence of performance and VfM; interpreting the evidence on an agreed basis; and presenting a clear and robust performance story. This guide sets out a framework for making and presenting judgements in a way that opens both the reasoning process and the evidence to scrutiny. The approach is designed to be used in alignment with broader monitoring, evaluation, and learning (MEL) systems—both for efficiency's sake, and to ensure conceptual coherence between VfM evaluation and wider MEL work. The VfM framework achieves these aims by: using explicit criteria (aspects of performance) and standards (levels of performance) to provide a transparent basis for making sound judgements about performance and VfM; combining quantitative and qualitative forms of evidence to support a richer and more nuanced understanding than can be gained from the use of indicators alone; accommodating economic evaluation (where feasible and appropriate) without limiting the analysis to economic methods and metrics alone; and incorporating and building on an approach to VfM evaluation which is familiar to international aid donors.